Vogelmädchen - O'Dell, Scott,Mitscha-Märheim, Christa (Ueberreuter, 1988)
A young Indian woman, accompanied by her infant and cruel husband, experiences joy and heartbreak when she joins the Lewis and Clark Expedition seeking a way to the Pacific.
EST: Streams to the river, river to the sea <dt.>
Keywords: Jugendbuch; Sacagawea <1786-1884>; Indianer; Indians of North America; Weiße; Expedition; Kultur